Silent Infarcts with Sickle Cell Anemia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The effect of transfusion therapy on the risk for new silent infarct or stroke in children with sickle cell anemia and abnormal transcranial Doppler (TCD) ultrasonography was determined at the University of Miami, FL, and other centers in the STOP trial (Stroke Prevention in Sickle Cell Anemia).